Trends in agro-byproducts and their feeding potential in sub-Saharan Africa - Bedingar, T.; Degefa, G. (International Livestock Centre for Africa, 1990)
Reviews macro-data on production and utilization of major agro-industrial byproducts in sub-Saharan Africa with, particularly attention on those involved in international trade; viz, molasses, groundnut cake, cottonseed cake, sunflower seed cake, palm kernel cake and fishmeal. Evaluates their feeding potential in relation to their nutritive values for cattle feeding systems in the sub-continent. Examines production and utilization of byproducts in West, Eastern, Central and Southern Africa. Illustrates production utilization, real export values, feed values and feeding potentials of byproducts by region. Includes data on production, utilization and nominal export values of byproducts by region.